Fractured Critical Awareness in ELF-Aware Teacher Education: Native-Speaker Ideology and Multicultural Competence among Turkish Pre-Service EFL Teachers - Çoban, Zelal; Selvi, Batuhan (IGI Global, 2026)
This chapter investigates Turkish pre-service EFL teachers’ multicultural competence through an explanatory sequential mixed-methods design. In the quantitative strand, 129 pre-service teachers at three Turkish state universities completed the Multicultural Competence Scale. Results yielded high self-reported competence but notably low internal consistency on the Awareness dimension. In the qualitative strand, semi-structured interviews with 15 purposively selected participants revealed a phenomenon termed fractured critical awareness: participants articulated sophisticated critiques of native-speaker hegemony and linguistic imperialism, yet they defaulted to British or American English in their own pedagogical decisions. These findings suggest that ELF-aware teacher education develops cognitive knowledge about linguistic plurality but does not reliably produce the identity-level transformation necessary for enacting ELF-informed pedagogy. © 2027 by IGI Global Scientific Publishing. All rights reserved.
Keywords: American English; British English; Internal Consistency; Level Transformation; Mixed Method; Preservice Teachers; Semi Structured Interviews; Teacher Education; Teachers'; Turkishs; Linguistics; Teaching